Internal structure of a coronal mass ejection revealed by Akatsuki radio occultation observations. Issue 7 (17th July 2015) - Ando, H.; Shiota, D.; Imamura, T.; Tokumaru, M.; Asai, A.; Isobe, H.; Päzold, M.; Häusler, B.; Nakamura, M.
Abstract A coronal mass ejection (CME) was observed at the heliocentric distance of 12.7 Rυ by radio occultation measurements using the Akatsuki spacecraft. The temporal developments of the bulk velocity and the electron column density along the raypath traversing the CME were obtained, and under the assumption that the irregularities are transported across the raypath, the internal structure of the CME covering the region from the core to the tail was retrieved. The suggested internal structure was compared with Large Angle Spectroscopic Coronagraph images, a numerical study and previous radio occultation observations of CMEs to propose a CME model; the bulk velocity and the electron density have relatively large values in the core, decrease behind the core, and increase again in the tail region where the fast plasma flow associated with the magnetic reconnection converges. This implies that the magnetic reconnection behind the CMEs might continue up to at least the heliocentric distance of ∼13 Rυ.